The Role of Probiotics in Improving Motor Function in Parkinson’s Disease: Evidence from a Systematic Review and Meta-Analysis - Andra Danika; Paulus Alexander Supit (The International Journal of Medical Science and Health Research, 2025)
Introduction: Parkinson’s disease (PD) is a progressive neurodegenerative disorder characterized by motor deterioration that profoundly impacts functional independence and quality of life. Recent advances suggest that the gut–brain axis contributes to PD pathophysiology, with gut dysbiosis potentially exacerbating neuroinflammation and α-synuclein pathology. Probiotics have emerged as a novel therapeutic approach, but their effect on motor outcomes remains uncertain. Objective: To evaluate the efficacy of probiotic supplementation in alleviating motor deterioration in PD, with Unified Parkinson’s Disease Rating Scale Part III (UPDRS III) scores as the primary outcome. Methods: A systematic review and meta-analysis were conducted in accordance with PRISMA 2020 guidelines. PubMed, Cochrane Library, and ScienceDirect were searched from inception to February 2025. Eligible studies were randomized controlled trials comparing probiotics with placebo or usual care in adults with PD. The primary outcome was mean change in UPDRS III scores. Risk of bias was assessed using the Cochrane RoB 2.0 tool, and certainty of evidence was graded with GRADE methodology. Random-effects models were applied to calculate pooled mean differences (MD) with 95% confidence intervals (CI). Results: From 294 records, five RCTs comprising 317 participants met the inclusion criteria. Pooled analysis demonstrated a significant improvement in motor function with probiotics compared to control (MD –3.15, 95% CI –5.76 to –0.54; p = 0.02). The direction of effect consistently favored probiotics across all trials, although heterogeneity was moderate (I² = 65%). Adverse events were infrequent and mild, primarily consisting of transient gastrointestinal discomfort. No serious probiotic-related adverse events were reported. Discussion: This analysis highlights the potential role of probiotics as a safe and accessible adjunctive strategy in PD management. The magnitude of improvement in UPDRS III exceeds the minimal clinically important difference, suggesting clinically meaningful benefits. Nevertheless, variability in probiotic formulations, small sample sizes, and short treatment durations limit generalizability. Integration of microbiome profiling and biomarker assessment in future trials may clarify mechanisms of action and identify patient subgroups most likely to benefit. Conclusion: Probiotic supplementation appears to provide a modest but clinically relevant improvement in motor function in PD, as measured by UPDRS III. While promising, further large, standardized, and long-term RCTs are required before probiotics can be integrated into routine PD care.